Cotidianizando a utopia: um estudo sobre as organização das atividades culturais e político-sociais dos anarco-punks em João Pessoa - Bastos, Yuriallis Fernandes (2008)
Tis work is consequence of a research based on the participant observation method, complemented by a posture of observant participation, which objective was to understand, through an analysis of cultural and polictic-social activities organized by7 two collective actor in the anarchic punk scene in João Pessoa city, the processes through which these, inspired in the punk culture and in the anarchist ideology, build in their movement an alternative autonomist and contra cultural of organization that is contradiction to the hierarchical and bureaucratic models of the current official politics. Also it contradicts the industrial culture and its mass culture. . Trying to understand the peculiar style of organization of activities and events propagandized by collective actors in the mentioned scene, it was made a theoretic debate among urban sociologists and anthropologists that study young cultures and social movements, including some that wrote about movements anarchist, punk and anarch-punk. In this research it was also analyzed militancy source materials, such as informative bulletins, reports of anarchpunk meeting of the northeast region of Brazil and websites of anarch-punk organizations. Based in the research efforts, we realized that the style of organization of the anarch-punk acting in the João Pessoa scene, creates a new style of actuation influenced however different of the styles anarchist and punk. That happens because it is mixed in their activities cultural and polictic-social elements and aspects that before is only found separated or absent in each of these two styles of actuation.